DOES FINANCIAL STATEMENT PUBLICATION EFFECT STOCK PRICE OF LQ-45 AT JAKARTA STOCK EXCHANGE - Muhammad Zilal Hamzah; Ihsanul Fatta (Indonesian Management and Accounting Research, 2007)
This article is purposed to know empirically wheather there is difference between stock price before and after the publicizing of financial statement of LQ-45 companies, listing at Jakarta Stock Exchange. Sample and data used in this analysis is all LQ-45 companies and 10 days stock price before and after financial statements are published. The finding shows that six variables such as return on equity, return on investment, price book value, price earning ratio, quick ratio and current ratio have significant and insignificant relationship toward stock price. According to the estimation can be concluded that all of those variables influence stock price 99.5% and however, most investor at Jakarta Stock Exchange are not consider to fundamental and internal factors in decision making process to buy or to sell a stock.Jel Classification: Keywords: Financial Statement, LQ-45 Stock Price